Morphology and viability test optimization in seeds of Passiflora spp. from Costa Rica - Vega-Corrales, Elizabeth (2022)
Introduction. In Costa Rica there are 51 native species of passion fruit plants that have commercial potential due to their phytochemical characteristics. In Passiflora the seminal characteristics can be used to taxonomically classify the genus species. The identification of plant material and the development of methodologies that enable quality assessment is essential for propagation, production, and conservation. Objective. To characterize Passiflora biflora and Passiflora adenopoda seeds based on their morphology and to optimize the protocol for determining their viability by means of the tetrazolium test. Materials and methods. Morphological characterization and viability trials were carried out in 2022, at the Centro de Investigaciones en Granos y Semillas (CIGRAS), Universidad de Costa Rica. Twelve external morphological characters and the internal structures of P. biflora and P. adenopoda were characterized. For the optimization of the tetrazolium test protocol, the effect of two types of cutting (longitudinal and angular), two concentrations of tetrazolium salt (0.5 % and 1 %), three temperatures (30, 35, and 40 ºC), and four incubation times (3, 6, 12, and 24 h) were assessed. Results. The morphological characters evaluated allowed the seeds to be classified as P. biflora and P. adenopoda. By using 1 % tetrazolium salt, a longitudinal cut, a temperature of 40 ºC, and an incubation time of 3 h, similar viability percentage was obtained (90 % in P. biflora and 91 % in P. adenopoda), and a staining of the same quality, as that obtained with the international standardized method. Conclusions. The seminal characteristics assessed allowed the classification of the analyzed seeds as P. biflora and P. adenopoda. In addition, the tetrazolium test protocol was optimized by reducing the incubation time from 24 to 3 hours.